The Effect of Earning Persistence and Growth Opportunities on Future Earning Response Coefficient with Public Ownership as Moderation - Sari, Pratiwi Nila (Green Publisher Indonesia, 2023)
The role of public ownership in moderating the effect of earning persistence and growth opportunities on the future earnings responses’ coefficient is the focus of this study. Understanding the background of these concepts provides context for the research. This study aims to determine the role of public ownership in moderating the effect of earning persistence and growth opportunities on future earnings responses coefficient. This research uses companies in the Consumer Cyclicals sector and the Consumer Non-Cyclicals sector during the 2018-2021 period. Sampling method with purposive sampling. The results of this study indicate that earnings persistence affects the Future Earning Responses Coefficient. Growth Opportunities have no effect on the Future Earning Responses Coefficient. The role of public ownership is able to strengthen the effect of earning persistence and Growth Opportunities on Future Earning Responses Coefficient.